Central bank digital currency as a payment method for tourists: application of the theory of planned behavior to digital Yuan/Won/Dollar choice - Radic, Aleksandar; Wei, Quan; Koo, Bonhak; Chua, Bee-Lia; Kim, Jinkyung Jenny; Han, Heesup (Routledge, 2022)
Central Bank Digital Currency (CBDC) is a digital asset backed to fiat currencies issued and regulated by reputable national financial institutions. Bearing in mind accelerating developments in financial technology and CBDC, this study explored tourists’ adoption of CBDC as a payment method by focusing on the relationship between attitudes, subjective norms, perceived behavioral control, mass media coverage, fear of missing out relative advantages, and perceived risk. A socio-psychological theory was utilized as a theoretical framework. The survey data were collected from China, Korea, and the US. The proposed framework strongly supported Digital Korean Won and Digital Yuen.